Associations between body composition and gut microbiota in female college students with and without dance training - Caifang Qiu; Hui Wang; Ran Liu (PLoS ONE, 2026)
Physical activity has been associated with gut microbiota variation and body composition phenotypes, but evidence in female dance students remains limited. This study compared body composition profiles and gut microbiota characteristics between female university students majoring in dance and those from non-dance majors. Seventy students were included (n = 35 per group). Body composition was assessed using bioelectrical impedance analysis (InBody 970), and fecal samples were analyzed by 16S rRNA gene sequencing. Dance students exhibited significantly lower adiposity related parameters and central fat accumulation indices, including PBF, BFM, FMI, VFA, VFL, WC, WHR, WHtR, ABSI, and conicity index ( P < 0.001), while showing higher SMM/WT, TBW/WT, and lower limb lean mass distribution ( P < 0.001). No significant differences were observed in FFM, SMM, or SMI ( P > 0.05). Gut microbiota composition differed between groups, with differential taxa observed across multiple taxonomic levels. Notably, Faecalibacterium and Lachnospiraceae_ND3007_group showed negative correlations with adiposity related indices and positive correlations with muscle and hydration related parameters, whereas Peptoniphilus , Ezakiella , and Fenollaria were positively correlated with adiposity related indices. In addition, Fusobacterium and Escherichia Shigella were positively associated with central adiposity measures. These findings indicate that female dance students exhibit distinct body composition profiles, while microbiome-related differences and associations appear modest and exploratory, warranting further validation in larger and well-controlled studies.